Development Strategy for Gluten-Free Milkfish Dimsum and Shrimp Head Waste Using BMC-SWOT Analysis - Slamet, Ahmad Haris Hasanuddin; Brillyantina, Septine; Syahnaz, Cindiah; Retnowati, Cicik (P3M Politeknik Negeri Jember, 2025)
Sidoarjo Regency is one of the centers of fishery production in East Java with superior products of milkfish and shrimp. Milkfish and shrimp head waste that has not been widely utilized in Sidoarjo Regency. On the other hand, the trend of healthy food consumption, especially gluten- free products, continues to increase both locally and globally. Efforts to overcome this problem can be done by developing a superior product in the form of gluten-free dimsum. Dimsum is a processed product that is widely favored by the public due to its practicality in serving. This study aimed to design a strategy for developing gluten-free dimsum from milkfish and shrimp heads using Canvas Business Model and SWOT analysis (Strengths, Weaknesses, Opportunities and Threats) . The first stage was the development of the business model canvas to illustrate the business potential of dimsum made from milkfish and shrimp head waste. The second stage was the analysis of the internal and external environment as the basis for the SWOT (Strength, Weakness, Opportunities, and Threaten) analysis. The results of the study indicated that gluten- free dim sum from milkfish and shrimp head waste has great potential for development. The analysis identified key strengths such as product innovation utilizing local resources, and key opportunities including the growing trend for healthy food. Conversely, high production costs were a primary weakness, with price competition from conventional products being a major threat. The Internal-External matrix analysis places this business venture in the 'Grow and Build' quadrant. Therefore, the recommended core strategy is an intensive approach focusing on market penetration through strong branding as a healthy, eco-friendly product and continuous product development.